We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
139
1
avatar

f(x) = atan(24.24/x)

g(x) = atan(16.92/x)

 

(f(x) - g(x))' = 0

 

(atan(24.24/x)-atan(16.92/x))' = 0

 

 

Help, please.

 Mar 22, 2019
 #1
avatar+28159 
+4

The following should help:

 

If y(x) = atan(k/x) where k is a constant, then dy/dx = -k/(k2 + x2)

 

 Mar 22, 2019
edited by Alan  Mar 22, 2019

19 Online Users

avatar